Pengembangan Media Video Tutorial Pembuatan Pola Busana Sekolah Mata Kuliah Busana Anak Jurusan Ilmu Kesejahteraan Keluarga FPP UNP - Hadzirotun Nadawiyah; Weni Nelmira (Program Studi Akuntansi IKOPIN, 2022)
In learning to make school clothing patterns, students still have difficulty in following the work steps of making school clothing patterns that are on this jobsheet, which is one of the obstacles experienced by students in learning to make school clothing patterns. This is the background for the author to conduct research on the development of learning media for making school clothing patterns in children's fashion courses. The purpose of this study is to produce learning media in the form of video tutorials for making school clothing patterns in children's clothing courses, as well as describing the validity and practicality of developing learning media for video tutorials for making school clothing patterns in children's fashion courses, Department of Family Welfare, Faculty of Tourism and Hospitality, University Padang Country. This study uses the Research and Development (R&D) method by applying the 4D model. The learning media developed was validated by 4 lecturers who are experts in the field of media and materials. At the practical stage, it is assessed by the course supervisor and students of Fashion Design Education Department of Family Welfare. The instrument used is an assessment sheet with a Likert scale. The data analysis technique used is descriptive quantitative data analysis. The product produced in this study is a video-based learning media tutorial for making school clothing patterns in children's clothing courses with the results of the media validation test getting a score of 93%, while the validation of the material expert gets a score of 84% so that a total score of 88.5% can be obtained with very valid category, while the results of the practicality test with the lecturer of the children's fashion subject obtained a score with a percentage of 90%, and the results of the practicality test based on the responses of small group students with a total of 10 students obtained a score of 92% in the very practical category, while the test results on a large group with 30 students obtained a score of 92% with a very practical category.